Accelerating heterogeneous nucleation to increase hardness and electrical conductivity by deformation prior to ageing for Cu-4 at.% Ti alloy. (3rd August 2019) - Han, Seung Zeon; Semboshi, Satoshi; Ahn, Jee Hyuk; Choi, Eun-Ae; Cho, Minah; Kadoi, Yusuke; Kim, Kwangho; Lee, Jehyun
ABSTRACT: Deformation bands, especially shear bands were intentionally formed in supersaturated Cu-4 at.% Ti alloy by groove-rolling with 75% area reduction. Cold deformation prior to the ageing process changed the precipitation behaviour of the alloy. The deformed structure with shear bands was maintained, without showing recovery and recrystallisation, even after prolonged ageing at 450°C for more than one day. The thermally stable shear bands act as nucleation initiation sites and prevent the expansion of discontinuous cellular precipitates. The hardness reached a value of 305 Hv and an electrical conductivity of 15% IACS (IACS = International Annealed Copper Standard. 100% IACS is defined as the conductivity corresponding to a volume resistivity at 20°C of 17.241 nΩ), compared to 283 Hv and 13% IACS for conventional solid-solutioned and peak-hardened alloy. In addition, the ageing time to reach the highest hardness was shortened from 720 to 180 min at 450°C.